Atypical uniportal thoracoscopic resection of a giant thymolipoma - Ulutaş, Hakkı; Çelik, Muhammet Reha; Akatlı, Ayşenur; Ağar, Mehmet; Gülçek, İlham; Şamdancı, Emine; İn, Erdal (My University, 2020)
Thymolipoma is a rare, slow-growing, benign anterior mediastinal tumor consisting of mature adipose tissue and thymic tissue. Herein we describe the case of a completely excised giant thymolipoma with uniportal video-assisted thoracoscopic surgery, which was detected incidentally on chest X-ray, with the review of the literature. A 30-year-old male patient was hospitalized to the department of general surgery with the diagnosis of appendicitis. Preoperative chest x-ray revealed mediastinal enlargement extending to the diaphragm at right paracardiac area where cardiac contours were erased and cardiomegaly-like appearance was observed. In the contrast-enhanced computed tomography of the chest, a massive mass of soft tissue was detected in fat density. The mediastinal lesion was completely excised with uniportal VATS. Histopathologically, the tumor was reported to be thymolipoma. Thymolipoma it should be totally removed with VATS surgery for both diagnosis and treatment.
Keywords: Patoloji; Cerrahi